Možnost uporabe odpadnega jedilnega olja za pridobivanje bioplina - Kolbl Repinc, Sabina (Acta hydrotechnica, 2021)
Anaerobic digestion is a process by which energy from organically degradable waste can be recovered in the form of biogas. The uncontrolled disposal of such organic waste is very burdensome to the environment. In Slovenia, large quantities of waste edible oils are produced every year, which could be used for biogas production. In this study, we investigated the methane potential of waste edible oil in a batch reactor. Further in the pilot scale in a semi-continuous experiment we evaluated the use of waste edible oil in anaerobic digesters of wastewater treatment plant. The results show that the quantity of oil per day that is fed into the anaerobic reactor is limited due to the process's instability and lower biogas production. The optimal daily organic loading of waste edible oil was between 1.6 and 2.4 g VS/L inoculum. During these conditions, the process of anaerobic digestion was stable and methane production was highest. At higher organic loading, the process became unstable, pH was reduced, volatile fatty acids increased, COD at the outflow of reactor increased, and biogas production was significantly reduced.
Keywords: anaerobic digestion; anaerobna presnova; biogas; bioplin; čistilna naprava; odpadno jedilno olje; odvečno blato; waste edible oil; wastewater sludge; wastewater treatment plant